A fine-grained analysis of the jumping to conclusions bias in schizophrenia: data-gathering, response confidence, and information integration - Andreas Glöckner; Steffen Moritz (Max Planck Institute for Research on Collective Goods, 2008)
Impaired decision behavior of schizophrenia patients has been repeatedly observed. We investigated the aspects of the jumping to conclusions bias (JTC): biases in information-gathering, information weighting and integration, and overconfidence, using the process tracing paradigm Mouselab, which allows for an in-depth exploration of various decision-making processes in a structured information environment. Although showing less focused and systematic information search, patients practically considered all pieces of information and showed no JTC in the sense of collecting less pieces of evidence. Choices of patients and controls both approximated a rational solution quite well, but patients showed more extreme and, in view of the ambiguous nature of the task, unjustified confidence. Both groups mainly used weighted additive decision strategies for information integration and only a small proportion relied on simple heuristics. Under high stress, induced by high affective valence plus time pressure, however, schizophrenia patients showed a less appropriate weighting of information and switched to equal weighting strategies. Patients that scored higher on the schizophrenia scale PANSS showed less information search and tended to rely more often on simple heuristics.
Keywords: H21; 610; Decision Making; Schizophrenia; Jump to conclusion; Heuristics; Psychische Störung; Entscheidung; Informationsverhalten; Verhaltensökonomik